Ultrahigh-hardness antistatic scratch-resistant polyurethane material

By introducing hydroxy silicone oil and modified chain extender into the polyurethane material, a uniform conductive network is formed and the use of ionic antistatic and wear-resistant capping agents is solved, and an ultra-high strength, wear-resistant, yellowing and antistatic polyurethane material is realized.

CN119529515APending Publication Date: 2025-02-28TUOCHUANG INTELLIGENT MFG (JIANGSU) CO LTD

Patent Information

Application Number
CN202411859474.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28

Smart Images

  • Figure BDA0005192823030000031
    Figure BDA0005192823030000031
  • Figure BDA0005192823030000032
    Figure BDA0005192823030000032
  • Figure BDA0005192823030000051
    Figure BDA0005192823030000051
Patent Text Reader

Abstract

The invention discloses an ultrahigh-hardness antistatic scratch-resistant polyurethane material, belongs to the technical field of polyurethane processing, and is used for solving the technical problem that the wear resistance and antistatic property of a polyurethane material in the prior art need to be further improved. The anti-static coating is prepared from raw materials in parts by weight as follows: 50-60 parts of composite polyurethane, 5-8 parts of modified filler, 20-30 parts of a curing agent, 3-5 parts of an antistatic agent, 3-5 parts of scratch-resistant filler, 3-5 parts of an ultraviolet absorbent, 3-5 parts of a dispersant, 0.5-2 parts of a light stabilizer and 0.5-2 parts of a rheological agent. The modified filler is prepared and used as a monomer, so that the modified chain extender is supported in the material, meanwhile, the compatibility of the modified chain extender and the material is improved, the modified end-capping reagent with the better ion number is synthesized, and the modified chain extender and a siloxane structure cooperate with each other to improve the mechanical performance of the material; and the modified end-capping agent and the modified chain extender cooperate to improve the antistatic performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane processing, in particular to an ultra-high hardness antistatic and scratch-resistant polyurethane material. Background Art

[0002] The development history of antistatic and wear-resistant polyurethane has evolved from the addition of traditional conductive fillers to functional technology innovation. Initially, the antistatic performance was improved by adding conductive fillers such as carbon black and metal powder, but the fillers easily lead to increased brittleness of the material and decreased wear resistance, limiting the application effect; subsequently, antistatic agent embedding technology was applied to polyurethane, but small molecule antistatic agents are easy to migrate, and the antistatic effect is not long-lasting; in recent years, ionic and permanent antistatic groups have been introduced into polyurethane to make the antistatic effect more stable and long-lasting. At the same time, the application of nanomaterials has brought breakthroughs, significantly improving the antistatic performance while maintaining wear resistance; in the future, antistatic and wear-resistant polyurethane will develop in the direction of environmental protection, high performance and composite materials to meet the needs of more industrial fields.

[0003] Prior art CN108178827B discloses an antistatic polyurethane elastomer and a preparation method thereof, which is made of the following raw materials: polymer polyol, isocyanate, chain extender, antioxidant, modified graphene, and catalyst. The modified graphene is added in the following manner: the modified graphene is added to the chain extender, and under ultrasonic conditions, a modified graphene-chain extender dispersion is formed, and groups such as hydroxyl, carboxyl, and amino groups on the surface of the modified graphene react with -NCO. The antistatic polyurethane elastomer obtained by an in-situ polymerization method has low surface resistivity and volume resistivity, high mechanical properties, good wear resistance and thermal stability, and can be applied to fields such as polyurethane textiles.

[0004] However, the above patent is to modify the graphene and cross-link it with a chain extender, then cross-link it with a chain extender and a polyurethane elastomer to introduce the modified graphene into the polyurethane material, so as to achieve the purpose of improving the antistatic performance of the material; however, due to the limitation of the material, the non-ionic antistatic agent graphene is easy to migrate to the surface of the material, resulting in the antistatic effect decreasing over time, and it does not form a chemical bond with the matrix material, and is easy to be gradually lost during cleaning, friction or aging, which weakens the antistatic property and significantly reduces the wear resistance of the material.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide an ultra-high hardness antistatic and scratch-resistant polyurethane material, so as to solve the technical problem that the wear resistance and antistatic performance of polyurethane materials in the prior art need to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: an ultra-high hardness antistatic scratch-resistant polyurethane material, the polyurethane material comprising the following raw materials in parts by weight: 50-60 parts of composite polyurethane, 5-8 parts of modified filler, 20-30 parts of curing agent, 3-5 parts of antistatic agent, 3-5 parts of scratch-resistant filler, 3-5 parts of ultraviolet absorber, 3-5 parts of dispersant, 0.5-2 parts of light stabilizer and 0.5-2 parts of rheological agent;

[0008] Wherein, the preparation method of composite polyurethane comprises the following steps:

[0009] A1, adding polytetrahydrofuran ether, hydroxy silicone oil, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle and stirring to obtain a prepolymer solution;

[0010] A2. Add the prepolymer liquid into the reactor, raise the temperature of the reactor to 50-60°C, drop 4,4'-dicyclohexylmethane diisocyanate solution into the reactor, keep warm for 40-60 minutes, add the modified chain extender into the reactor, keep warm for 20-30 minutes, add the modified end-capping agent into the reactor, keep warm for 90-120 minutes, and post-treat to obtain the composite polyurethane.

[0011] The reaction equation for preparing composite polyurethane is:

[0012]

[0013] Where:

[0014]

[0015] The reaction principle for preparing the composite polyurethane is as follows: in the reaction process, 4,4'-dicyclohexylmethane diisocyanate is used as a crosslinking agent. Under the condition of a catalyst, the isocyanate group on isophorone diisocyanate acts as an active group to condense with the hydroxyl groups on polytetramethylene furan ether and hydroxyl silicone oil to form a polyurethane prepolymer co-embedded with a polyethylene glycol segment and a polysiloxane segment. The multi-active hydroxyl groups on the modified chain extender can react with the isocyanate group on the polyurethane prepolymer, promote the polyurethane prepolymer to react with the active hydroxyl groups on the modified end-capping agent after esterification and crosslinking, and form a composite polyurethane co-embedded with a polytetramethylene furan ether segment and a polysiloxane segment and a modified end-capping agent having an ionic antistatic agent structure.

[0016] Furthermore, the curing agent is one or more of triethylene isocyanate, hexamethylene diisocyanate and toluene diisocyanate; the antistatic agent is one or more of dimethyl dioleyl ammonium methyl sulfate, polyaniline and carbon nanotubes; the scratch-resistant filler is one or more of nano-silica, alumina and nano-zirconium oxide; the ultraviolet absorber is one or more of dihydroxybenzophenone, bis-(2-hydroxyphenyl)-triazine and 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole; the dispersant is one or more of nonylphenol polyoxyethylene ether, polyethylene glycol monoether and polyethyleneimine; the light stabilizer is one or more of diisopropyl thiodipropyl dilaurate, dioctadecyl thiodipropyl distearate and tetramethyl thiosuccinate; the rheological agent is one or more of organic montmorillonite, environmentally friendly polyamide rheological agent and bentonite thickener.

[0017] Further, in step A1, the stirring rate of the reactor is 80-120rpm, the amount ratio of polytetrahydrofuran ether, hydroxy silicone oil, N,N-dimethylformamide and dibutyltin dilaurate is 4-5g:3-4g:25-30mL:0.1-0.3g, the molecular weight of polytetrahydrofuran ether is 950-1050, and the molecular weight of hydroxy silicone oil is 500-600; in step A2, the prepolymer solution, 4,4'-dicyclohexylmethane diisocyanate solution, modified chain extender The dosage ratio of the agent and the modified end-capping agent is 20-25mL:12-15g:5-8g:2-3g, and the 4,4'-dicyclohexylmethane diisocyanate solution is prepared by configuring 4,4'-dicyclohexylmethane diisocyanate and N,N-dimethylformamide in a weight ratio of 1:1. The post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added into a rotary evaporator with a water bath temperature of 80-100°C, and the composite polyurethane is obtained by reduced pressure distillation until no liquid is extracted.

[0018] Furthermore, the preparation method of the modified chain extender comprises the following steps:

[0019] B1. Add the modified filler, methacryloyloxyethyl trimethylammonium chloride, hydroxyethyl methacrylate and anhydrous ethanol into a reactor, introduce nitrogen protection, stir at room temperature for 10-15 minutes, then drop the initiator, raise the temperature of the reactor to 70-75°C, and keep warm for 2-4 hours to obtain a polymerization solution;

[0020] B2. Transfer the polymerization solution to a rotary evaporator, raise the temperature of the rotary evaporator to 80-100° C., remove 80% anhydrous ethanol by rotary evaporation to obtain a reaction solution, transfer the reaction solution to toluene, let it stand for 1-2 hours, and post-treat to obtain a modified chain extender.

[0021] The reaction equation for preparing the modified chain extender is:

[0022]

[0023] The reaction principle for preparing the modified chain extender is as follows: under the initiation of free radical catalyst and high temperature, the double bonds of the modified filler, methacryloyloxyethyl trimethyl ammonium chloride and hydroxyethyl methacrylate are broken, a free radical addition reaction occurs, and the modified chain extender is prepared through continuous polymerization.

[0024] Furthermore, in step B1, the amount ratio of modified filler, methacryloyloxyethyl trimethylammonium chloride, hydroxyethyl methacrylate, anhydrous ethanol and initiator is 4-6g:8-10g:2-3g:60-70mL:10-12mL, and the initiator is prepared by mixing azobisisobutyronitrile and ethanol in a weight ratio of 1:1; in step B2, the amount ratio of reaction solution and toluene is 2-3mL:5-6mL, and post-treatment includes: after standing, the reaction kettle is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction solution is distilled under reduced pressure until no liquid is extracted to obtain a modified chain extender.

[0025] Furthermore, the preparation method of the capping agent is: octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, 2,3-epoxypropyl trimethyl ammonium chloride, acetic acid and ethanol are added to a reactor and stirred, the temperature of the reactor is increased to 40-60°C, the reaction is kept warm for 2-4 hours, and the modified capping agent is obtained by post-treatment.

[0026] The reaction equation for preparing the modified end-capping agent is:

[0027]

[0028] Where:

[0029]

[0030] The reaction principle for preparing the modified end-capping agent is as follows: under the catalysis of acetic acid, the epoxy group on 2,3-epoxypropyltrimethylammonium chloride is ring-opened to generate free radicals, which react with the hydroxyl group on octadecyldimethylhydroxyethyl quaternary ammonium nitrate to finally prepare the modified end-capping agent.

[0031] Furthermore, the stirring rate of the reactor is 80-120rpm, the amount ratio of the octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and 2,3-epoxypropyltrimethylammonium chloride is 1mol:1mol, and the amount ratio of the octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, acetic acid and ethanol is 8-10g:2-3mL:30-40mL. The post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain a modified end-capping agent.

[0032] Furthermore, the preparation method of the modified filler comprises the following steps:

[0033] C1. Add tetraethoxysilane and anhydrous ethanol into a reaction kettle and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reaction kettle rises to 40-60°C, use 1-1.5 mol / L ammonia solution to adjust the pH of the system to 8-9, and keep warm for 24-36 hours to obtain a silicon-based gel.

[0034] C2, transferring the silicon-based gel to a tube furnace for calcination to obtain a silicon dioxide polymer, grinding it and passing it through a 400-600 mesh sieve to obtain a modified filler precursor;

[0035] C3. Add the modified filler precursor, 3-(methacryloyloxy)propyltrimethoxysilane, saturated sodium hydroxide solution and ethanol into the reactor, increase the temperature of the reactor to 30-50° C., keep the temperature for 3-5 hours, and post-treat to obtain the modified filler.

[0036] The reaction equation for preparing the modified filler is:

[0037]

[0038] The reaction principle for preparing the modified filler is as follows: under alkaline conditions, the siloxane on 3-(methacryloyloxy)propyltrimethoxysilane is hydrolyzed to produce a silanol structure, which undergoes an elimination reaction with the hydroxyl group on the surface of the modified filler precursor, and finally the modified filler is prepared.

[0039] Furthermore, in step C1, the stirring rate of the reactor is 80-120rpm, and the amount ratio of tetraethoxysilane, anhydrous ethanol and deionized water is 3-6g:30-40mL:10-20mL; in step C2, the calcination operation includes: after nitrogen protection is introduced, the tubular furnace is heated to 450-500°C at a heating rate of 5°C / min, and the silica polymer is obtained after calcination for 4-6h; in step C3, the amount ratio of the modified filler precursor, 3-(methacryloyloxy)propyltrimethoxysilane, saturated sodium hydroxide solution and ethanol is 6-8g:2-3g:0.3-0.5g:30-40mL, and the post-treatment includes: filtering the reaction solution, collecting the filter cake, washing it with anhydrous ethanol and deionized water for 3-5 times, and then placing the filter cake in a drying oven at a temperature of 60°C and vacuum drying it until the filter cake has a constant weight to obtain an inorganic crosslinking agent.

[0040] Furthermore, the preparation method of the polyurethane material comprises the following steps:

[0041] S1, adding composite polyurethane, modified filler, curing agent, antistatic agent, scratch-resistant filler, ultraviolet absorber, dispersant, light stabilizer and rheological agent into a reaction kettle and stirring evenly to obtain a mixture;

[0042] S2, adding the mixed material into a twin-screw extruder for melt extrusion to obtain a polyurethane material.

[0043] Furthermore, in step S2, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, and 220°C, respectively, and the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150bar.

[0044] Beneficial Effects

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The present invention uses hydroxy silicone oil as a composite polyurethane segment, wherein a large amount of siloxane structures significantly improve the mechanical properties of the material itself, and at the same time, its unique antioxidant ability and UV resistance significantly enhance the anti-yellowing performance of the material, and prepares a modified filler that is more compatible with the polyurethane segment and serves as a monomer of a modified chain extender, so that the modified chain extender is supported in the material and the compatibility of the modified filler and the material is improved, so that the filler is distributed more evenly, and the antistatic agent on the modified chain extender forms a more uniform conductive network, and by synthesizing an ionic antistatic agent capping agent with a better number of ions, the modified chain extender and the siloxane structure in the polyurethane segment cooperate to improve the mechanical properties of the material, and the modified end capping agent, the modified chain extender and the siloxane structure in the polyurethane segment cooperate to improve the anti-yellowing performance of the material, and finally a wear-resistant, anti-yellowing, anti-tensile and antistatic ultra-high strength polyurethane material is prepared.

[0047] 2. The present invention also prepares a modified filler by hydrolysis, modifies a large number of double bond structures on its surface, and uses it as a polymerization monomer to participate in the preparation of a modified chain extender. After modification with a silane coupling agent, the affinity of the modified filler with the remaining polymerization monomers is significantly improved, thereby improving the efficiency of the polymerization reaction. In addition, due to the supporting effect of the modified filler and its affinity with the siloxane structure in the polyurethane chain segment, the dispersibility of the modified chain extender in the material is significantly improved. In addition, the polymer long chain structure of the modified chain extender directly contributes to longer molecular segments in the chain extension reaction, significantly increasing the molecular weight of the polymer, thereby improving the toughness of the polymer, and significantly improving the tensile properties of the material. In addition, the antistatic agent on the modified chain extender forms a more uniform conductive network. The polymer structure provides a stronger support for the polyurethane chain segment and coordinates with the inorganic filler to significantly enhance the hardness of the material, ultimately significantly improving the wear resistance, tensile strength and hardness of the material.

[0048] 3. The present invention also prepares an ionic antistatic agent capping agent with a better number of ions by using an ionic antistatic agent. Through the better number of ions, a uniform conductive network is formed. The denser the ion conduction path, the stronger the conductivity, the easier it is to discharge static charge, and the stronger the antistatic performance. In addition, it forms a stable ion distribution on the surface and inside of the material by acting as a capping agent. When the surface is rubbed or lightly cleaned, its antistatic performance can still remain stable; the improvement of antistatic performance reduces the accumulation of static charge and weakens the local thermal effect caused. It cooperates with the siloxane segments and modified fillers in the material to improve the material's anti-yellowing performance. After the ionic antistatic agent absorbs environmental moisture, a thin water film will form on the surface of the material. This water film can dilute the surface oxidant concentration and reduce the oxidation reaction rate, thereby reducing yellowing. It cooperates with the modified chain extender to significantly improve the material's antistatic and anti-yellowing properties. DETAILED DESCRIPTION

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The polytetramethylene oxide used in the present invention is BASF polytetramethylene oxide, purchased from Shanghai Jingge Momentum New Material Technology Co., Ltd., with the product number of PTMEG1000;

[0051] The octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate used in the present invention is purchased from Linyi Guoli Chemical Co., Ltd., and the product number is antistatic agent SN;

[0052] The 4,4'-dicyclohexylmethane diisocyanate used in the present invention was purchased from Wanhua Chemical Group Co., Ltd. under the product number HMDI.

[0053] Example 1

[0054] This embodiment provides a method for preparing an ultra-high hardness antistatic and scratch-resistant polyurethane material, comprising the following steps:

[0055] S1. Preparation of Inorganic Crosslinking Agent

[0056] Weigh: 8.4 g of tetraethoxysilane and 64.0 mL of anhydrous ethanol were added to a reactor and stirred at a stirring rate of 80 rpm. After stirring at room temperature for 15 min, 32.0 mL of deionized water was added dropwise. After the temperature of the reactor was raised to 40° C., a 1.0 mol / L ammonia solution was used to adjust the pH of the system to 8, and the temperature was kept for 24 h to obtain a silicon-based gel;

[0057] The silica gel was transferred to a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 450°C at a heating rate of 5°C / min, and the silica polymer was obtained after being kept at this temperature for 4 hours. After grinding, the silica polymer was passed through a 400-mesh sieve to obtain a modified filler precursor.

[0058] Weigh: 12.4 g of modified filler precursor, 5.4 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.8 g of saturated sodium hydroxide solution and 72.0 mL of ethanol and add them into the reactor. The temperature of the reactor is raised to 30°C and kept warm for 3 hours. The reaction liquid is filtered and the filter cake is collected. After washing three times with anhydrous ethanol and deionized water, the filter cake is placed in a drying oven at 60°C and vacuum dried until the filter cake has constant weight to obtain an inorganic crosslinking agent.

[0059] S2. Preparation of modified chain extender

[0060] Weigh: 10.0 g of azobisisobutyronitrile and 10.0 g of ethanol to prepare an initiator;

[0061] Weigh: 10.0 g of modified filler, 16.0 g of methacryloyloxyethyl trimethylammonium chloride, 5.4 g of hydroxyethyl methacrylate and 120.0 mL of anhydrous ethanol, add into a reactor, introduce nitrogen protection, stir at room temperature for 10 min, then drop 20.0 mL of initiator, raise the temperature of the reactor to 70° C., and keep warm for 2 h to obtain a polymerization solution;

[0062] Weigh: 200.0mL of the polymerization solution is transferred to a rotary evaporator, the temperature of the rotary evaporator is increased to 80°C, 80% anhydrous ethanol is removed by rotary evaporation to obtain a reaction solution, the reaction solution is transferred to 500.0mL of toluene, and allowed to stand for 1h. After the reaction kettle is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is extracted to obtain a modified chain extender.

[0063] S3. Preparation of composite polyurethane

[0064] Weigh: 40.4g of octadecyldimethylhydroxyethyl quaternary ammonium nitrate, 15.1g of 2,3-epoxypropyltrimethylammonium chloride, 10.0mL of acetic acid and 150.0mL of ethanol are added to a reactor and stirred at a stirring rate of 80rpm. The temperature of the reactor is raised to 40°C and the reaction is kept warm for 2h. After the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and the reaction liquid is distilled under reduced pressure until no liquid is extracted to obtain a modified end-capping agent;

[0065] Weigh: 12.0 g of polytetrahydrofuran ether with a molecular weight of 950, 9.0 g of hydroxy silicone oil with a molecular weight of 500, 75.0 mL of N,N-dimethylformamide and 0.8 g of dibutyltin dilaurate, add into a reaction kettle and stir at a stirring rate of 80 rpm to obtain a prepolymer solution;

[0066] Weigh: 10.0 g of 4,4'-dicyclohexylmethane diisocyanate and 10. g of N,N-dimethylformamide to prepare a 4,4'-dicyclohexylmethane diisocyanate solution;

[0067] Weigh: 20.0 mL of prepolymer liquid is added to the reactor, the temperature of the reactor is raised to 50°C, 12.0 g of 4,4'-dicyclohexylmethane diisocyanate solution is added dropwise to the reactor, and the reaction is kept warm for 40 minutes. 6.4 g of modified chain extender is added to the reactor, and the reaction is kept warm for 20 minutes. 2.4 g of modified end-capping agent is added to the reactor, and the reaction is kept warm for 90 minutes. Composite polyurethane is obtained by post-treatment.

[0068] S4. Preparation of polyurethane material

[0069] Weigh: 54.0 g of composite polyurethane, 5.4 g of modified filler, 24.0 g of triethylene isocyanate, 3.6 g of dimethyl dioleyl ammonium methyl sulfate, 3.6 g of nano silicon dioxide, 3.6 g of 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, 3.6 g of nonylphenol polyoxyethylene ether, 1.2 g of diisopropyl dilaurate thiodipropyl ester and 1.2 g of environmentally friendly polyamide rheological agent, add into a reaction kettle, stir evenly and obtain a mixture;

[0070] The mixed material is added into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, and 220°C, respectively. The main engine speed of the twin-screw extruder is 80 rpm, the pressure is 100 bar, and the polyurethane material is obtained by melt extrusion.

[0071] Example 2

[0072] This embodiment provides a method for preparing an ultra-high hardness antistatic and scratch-resistant polyurethane material, comprising the following steps:

[0073] S1. Preparation of Inorganic Crosslinking Agent

[0074] Weigh: 8.4 g of tetraethoxysilane and 64.0 mL of anhydrous ethanol were added to a reactor and stirred at a stirring rate of 120 rpm. After stirring at room temperature for 20 min, 30.0 mL of deionized water was added dropwise. After the temperature of the reactor was raised to 60° C., a 1.5 mol / L ammonia solution was used to adjust the system pH to 9, and the temperature was kept for 36 h to obtain a silicon-based gel;

[0075] The silica gel was transferred to a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 500°C at a heating rate of 5°C / min, and the silica polymer was obtained after calcination for 6 hours, and the modified filler precursor was obtained after grinding and passing through a 600-mesh sieve;

[0076] Weigh: 12.4 g of modified filler precursor, 5.4 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.8 g of saturated sodium hydroxide solution and 64.0 mL of ethanol and add them to the reactor. The temperature of the reactor is raised to 50°C and kept warm for 5 hours. The reaction liquid is filtered and the filter cake is collected. After washing 5 times with anhydrous ethanol and deionized water, the filter cake is placed in a drying oven at 60°C and vacuum dried until the filter cake has constant weight to obtain an inorganic crosslinking agent.

[0077] S2. Preparation of modified chain extender

[0078] Weigh: 10.0 g of azobisisobutyronitrile and 10.0 g of ethanol to prepare an initiator;

[0079] Weigh: 8.4 g of modified filler, 18.0 g of methacryloyloxyethyl trimethylammonium chloride, 5.4 g of hydroxyethyl methacrylate and 120.0 mL of anhydrous ethanol, add into a reactor, introduce nitrogen protection, stir at room temperature for 15 min, then drop 20.0 mL of initiator, raise the temperature of the reactor to 75° C., and keep warm for 4 h to obtain a polymerization solution;

[0080] Weigh: 250.0 mL of the polymerization solution was transferred to a rotary evaporator, the temperature of the rotary evaporator was increased to 80°C, 80% anhydrous ethanol was removed by rotary evaporation to obtain a reaction solution, the reaction solution was transferred to 550.0 mL of toluene, and allowed to stand for 2 h. After the reaction kettle was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 100°C, and reduced pressure distillation was performed until no liquid was extracted to obtain a modified chain extender.

[0081] S3. Preparation of composite polyurethane

[0082] Weigh: 40.4g of octadecyldimethylhydroxyethyl quaternary ammonium nitrate, 15.1g of 2,3-epoxypropyltrimethylammonium chloride, 12.0mL of acetic acid and 160.0mL of ethanol are added to a reactor and stirred at a stirring rate of 80rpm. The temperature of the reactor is raised to 60°C and the reaction is kept warm for 4h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and the reaction liquid is distilled under reduced pressure until no liquid is extracted to obtain a modified end-capping agent;

[0083] Weigh: 40.0 g of polytetrahydrofuran ether with a molecular weight of 1050, 30.0 g of hydroxy silicone oil with a molecular weight of 600, 250.0 mL of N,N-dimethylformamide and 1.2 g of dibutyltin dilaurate, add into a reaction kettle and stir at a stirring rate of 120 rpm to obtain a prepolymer solution;

[0084] Weigh: 10.0 g of 4,4'-dicyclohexylmethane diisocyanate and 10.0 g of N,N-dimethylformamide to prepare a 4,4'-dicyclohexylmethane diisocyanate solution;

[0085] Weigh: 24.0 mL of prepolymer liquid is added to the reactor, the temperature of the reactor is raised to 60°C, 12.4 g of 4,4'-dicyclohexylmethane diisocyanate solution is added dropwise to the reactor, and the reaction is kept warm for 60 minutes. 6.4 g of modified chain extender is added to the reactor, and the reaction is kept warm for 30 minutes. 2.4 g of modified end-capping agent is added to the reactor, and the reaction is kept warm for 120 minutes. Composite polyurethane is obtained by post-treatment.

[0086] S4. Preparation of polyurethane material

[0087] Weigh: 54.0 g of composite polyurethane, 7.2 g of modified filler, 24.0 g of triethylene isocyanate, 3.6 g of dimethyl dioleyl ammonium methyl sulfate, 3.6 g of nano silicon dioxide, 3.6 g of 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, 4.2 g of nonylphenol polyoxyethylene ether, 1.6 g of diisopropyl dilaurate thiodipropyl ester and 1.6 g of environmentally friendly polyamide rheological agent, add into a reaction kettle, stir evenly and obtain a mixture;

[0088] The mixed material is added into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, and 220°C, respectively. The main engine speed of the twin-screw extruder is 120rpm, and the pressure is 150bar. The polyurethane material is obtained by melt extrusion.

[0089] Example 3

[0090] This embodiment provides a method for preparing an ultra-high hardness antistatic and scratch-resistant polyurethane material, comprising the following steps:

[0091] S1. Preparation of Inorganic Crosslinking Agent

[0092] Weigh: 10.0 g of tetraethoxysilane and 72.0 mL of anhydrous ethanol were added to a reactor and stirred at a stirring rate of 100 rpm. After stirring at room temperature for 18 min, 32.0 mL of deionized water was added dropwise. After the temperature of the reactor was raised to 50° C., a 1.2 mol / L ammonia solution was used to adjust the system pH to 9, and the temperature was kept for 30 h to obtain a silicon-based gel;

[0093] The silica gel was transferred to a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 475°C at a heating rate of 5°C / min, and the silica polymer was obtained after being kept at this temperature for 5 hours. After grinding, the silica polymer was passed through a 500-mesh sieve to obtain a modified filler precursor.

[0094] Weigh: 12.4 g of modified filler precursor, 5.4 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.8 g of saturated sodium hydroxide solution and 64.0 mL of ethanol and add them into the reactor. The temperature of the reactor is raised to 40°C and kept warm for 4 hours. The reaction liquid is filtered and the filter cake is collected. After washing 4 times with anhydrous ethanol and deionized water, the filter cake is placed in a drying oven at 60°C and vacuum dried until the filter cake has constant weight to obtain an inorganic crosslinking agent.

[0095] S2. Preparation of modified chain extender

[0096] Weigh: 12.0 g of azobisisobutyronitrile and 12.0 g of ethanol to prepare an initiator;

[0097] Weigh: 10.0 g of modified filler, 18.0 g of methacryloyloxyethyl trimethylammonium chloride, 5.4 g of hydroxyethyl methacrylate and 120.0 mL of anhydrous ethanol, add into a reactor, introduce nitrogen protection, stir at room temperature for 12 min, then dropwise add 21.0 mL of initiator, raise the temperature of the reactor to 75° C., and keep warm for 3 h to obtain a polymerization solution;

[0098] Weigh: 24.0 mL of the polymerization solution was transferred to a rotary evaporator, the temperature of the rotary evaporator was increased to 90°C, 80% anhydrous ethanol was removed by rotary evaporation to obtain a reaction solution, the reaction solution was transferred to 54.0 mL of toluene, and allowed to stand for 2 h. After the reaction kettle was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 90°C, and vacuum distilled until no liquid was extracted to obtain a modified chain extender.

[0099] S3. Preparation of composite polyurethane

[0100] Weigh: 40.4g of octadecyldimethylhydroxyethyl quaternary ammonium nitrate, 15.1g of 2,3-epoxypropyltrimethylammonium chloride, 12.4mL of acetic acid and 160.0mL of ethanol are added to a reactor and stirred at a stirring rate of 100rpm. The temperature of the reactor is raised to 50°C and the reaction is kept warm for 3h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain a modified end-capping agent;

[0101] Weigh: 45.0 g of polytetrahydrofuran ether with a molecular weight of 1000, 36.0 g of hydroxy silicone oil with a molecular weight of 550, 250.0 mL of N,N-dimethylformamide and 2.4 g of dibutyltin dilaurate, add into a reaction kettle and stir at a stirring rate of 100 rpm to obtain a prepolymer solution;

[0102] Weigh: 10.0 g of 4,4'-dicyclohexylmethane diisocyanate and 10.0 g of N,N-dimethylformamide to prepare a 4,4'-dicyclohexylmethane diisocyanate solution;

[0103] Weigh: 24.0 mL of prepolymer liquid is added to the reactor, the temperature of the reactor is raised to 55°C, 12.4 g of 4,4'-dicyclohexylmethane diisocyanate solution is added dropwise to the reactor, and the reaction is kept warm for 50 minutes. 7.0 g of modified chain extender is added to the reactor, and the reaction is kept warm for 24 minutes. 2.4 g of modified end-capping agent is added to the reactor, and the reaction is kept warm for 100 minutes. Composite polyurethane is obtained by post-treatment.

[0104] S4. Preparation of polyurethane material

[0105] Weigh: 54.0 g of composite polyurethane, 6.4 g of modified filler, 24.0 g of triethylene isocyanate, 4.8 g of dimethyl dioleyl ammonium methyl sulfate, 3.6 g of nano silicon dioxide, 4.8 g of 2-(2'-hydroxy-5'-octylphenyl)-benzotriazole, 4.2 g of nonylphenol polyoxyethylene ether, 1.6 g of diisopropyl dilaurate thiodipropyl ester and 1.6 g of environmentally friendly polyamide rheological agent, add into a reaction kettle, stir evenly and obtain a mixture;

[0106] The mixed material is added into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 200°C, 200°C, 205°C, 215°C, 215°C, 220°C, and 220°C, respectively. The main engine speed of the twin-screw extruder is 100 rpm, and the pressure is 125 bar. The polyurethane material is obtained by melt extrusion.

[0107] Comparative Example 1

[0108] The difference between this comparative example and Example 3 is that the step of preparing the inorganic crosslinking agent in step S1 is eliminated, and triallylamine is used in an equal amount to replace the inorganic crosslinking agent in the process of preparing the modified chain extender.

[0109] Comparative Example 2

[0110] The difference between this comparative example and Example 3 is that the step of preparing the modified chain extender in step S1 is eliminated, and an equal amount of triethanolamine is used to replace the modified chain extender in the process of preparing the composite polyurethane.

[0111] Comparative Example 3

[0112] The difference between this comparative example and Example 3 is that the step of preparing the modified end-capping agent in step S2 is eliminated, and an equal amount of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate is used to replace the modified end-capping agent in the process of preparing the composite polyurethane.

[0113] Performance Test:

[0114] The hardness of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 2411-2008 "Determination of indentation hardness (Shore hardness) of plastics and hard rubber using a hardness tester";

[0115] The volume wear of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method)";

[0116] The yellowing resistance grades of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 41793-2022 "Test methods for artificial leather and synthetic leather - Determination of potential phenolic yellowing";

[0117] The elongation at break of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard HG / T 5500-2019 "Thermoplastic Polyurethane (TPU) Granules";

[0118] The antistatic properties of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 15662-1995 “Test method for volume resistivity of conductive and antistatic plastics”. The specific data are shown in Table 1.

[0119] Table 1-Performance test data of each sample

[0120]

[0121]

[0122] Data Analysis:

[0123] The data in Table 1 are compared and analyzed. The hardness of the polyurethane material prepared by the present invention is 72D and the volume wear is 30mm. 3 , yellowing resistance grade is 5, elongation at break is 367% and volume resistivity is 3.1×10 7 Ω·m, all data are better than those of the comparative example;

[0124] By comparing the data of Example 3, Comparative Example 1 and Comparative Example 2, it can be found that the hardness, wear resistance and tensile strength of the polyurethane material are significantly reduced, indicating that the modified filler is lacking as the support of the polymer modified chain extender, and the dispersibility of the modified chain extender in the material is significantly reduced, resulting in a weakened chain extension effect, thereby causing the mechanical properties and hardness of the material to decrease. In addition, compared with the small molecule chain extender, the polymer chain extender component extends the length of the matrix molecular chain through its polymer chain structure, improves the flexibility and mechanical properties of the polymer, such as toughness, impact resistance and elongation at break, so that the mechanical properties of the material are significantly improved;

[0125] By comparing the data of Example 3 and Comparative Example 3, it can be found that the yellowing resistance grade and volume resistivity of the polyurethane material are significantly increased, indicating that the modified end-capping agent prepared by the present invention has a better number of ions than the single-component ionic antistatic agent, forming a uniform conductive network, the denser the ion conduction path, the stronger the conductivity, the easier it is to discharge static charge, and the stronger the antistatic performance. In addition, the improvement of antistatic performance reduces the accumulation of static charge and weakens the local thermal effect, and cooperates with the siloxane segment and modified filler in the material to improve the anti-yellowing performance of the material.

[0126] The present invention prepares a modified filler and uses it as a monomer of a modified chain extender, so that the modified chain extender is supported in the material and the compatibility of the modified filler and the material is improved, so that the filler is distributed more evenly, and the antistatic agent on the modified chain extender forms a more uniform conductive network, and an ionic antistatic agent capping agent with a better number of ions is synthesized, and the modified chain extender and the siloxane structure in the polyurethane segment cooperate to improve the mechanical properties of the material, and the modified capping agent, the modified chain extender and the siloxane structure in the polyurethane segment cooperate to improve the anti-yellowing performance of the material, and finally a wear-resistant, anti-yellowing, anti-tensile and anti-static ultra-high strength polyurethane material is prepared.

[0127] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. Ultra-high hardness antistatic and scratch-resistant polyurethane material, characterized in that: The polyurethane material comprises the following raw materials in parts by weight: 50-60 parts of composite polyurethane, 5-8 parts of modified filler, 20-30 parts of curing agent, 3-5 parts of antistatic agent, 3-5 parts of scratch-resistant filler, 3-5 parts of ultraviolet absorber, 3-5 parts of dispersant, 0.5-2 parts of light stabilizer and 0.5-2 parts of rheological agent; Wherein, the preparation method of composite polyurethane comprises the following steps: A1, adding polytetrahydrofuran ether, hydroxy silicone oil, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle and stirring to obtain a prepolymer solution; A2. Add the prepolymer liquid into the reactor, raise the temperature of the reactor to 50-60°C, drop 4,4'-dicyclohexylmethane diisocyanate solution into the reactor, keep warm for 40-60 minutes, add the modified chain extender into the reactor, keep warm for 20-30 minutes, add the modified end-capping agent into the reactor, keep warm for 90-120 minutes, and post-treat to obtain the composite polyurethane.

2. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 1, characterized in that: In step A1, the stirring rate of the reactor is 80-120rpm, the amount ratio of polytetrahydrofuran ether, hydroxy silicone oil, N,N-dimethylformamide and dibutyltin dilaurate is 4-5g:3-4g:25-30mL:0.1-0.3g, the molecular weight of polytetrahydrofuran ether is 950-1050, and the molecular weight of hydroxy silicone oil is 500-600; in step A2, the amount ratio of prepolymer liquid, 4,4'-dicyclohexylmethane diisocyanate solution, modified chain extender and modified end capping group is 20-25mL:12-15g:5-8g:2-3g, and 4,4'-dicyclohexylmethane diisocyanate solution is prepared by mixing 4,4'-dicyclohexylmethane diisocyanate and N,N-dimethylformamide in a weight ratio of 1:

1.

3. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 1, characterized in that: The preparation method of the modified chain extender comprises the following steps: B1. Add the modified filler, methacryloyloxyethyl trimethylammonium chloride, hydroxyethyl methacrylate and anhydrous ethanol into a reactor, introduce nitrogen protection, stir at room temperature for 10-15 minutes, then drop the initiator, raise the temperature of the reactor to 70-75°C, and keep it warm for 2-4 hours to obtain a polymerization solution; B2. Transfer the polymerization solution to a rotary evaporator, raise the temperature of the rotary evaporator to 80-100° C., remove 80% anhydrous ethanol by rotary evaporation to obtain a reaction solution, transfer the reaction solution to toluene, let it stand for 1-2 hours, and post-treat to obtain a modified chain extender.

4. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 3, characterized in that: In step B1, the amount ratio of modified filler, methacryloyloxyethyl trimethylammonium chloride, hydroxyethyl methacrylate, anhydrous ethanol and initiator is 4-6g:8-10g:2-3g:60-70mL:10-12mL, and the initiator is prepared by mixing azobisisobutyronitrile and ethanol in a weight ratio of 1:1; in step B2, the amount ratio of reaction solution and toluene is 2-3mL:5-6mL.

5. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 1, characterized in that: The preparation method of the end-capping agent is as follows: octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, 2,3-epoxypropyl trimethyl ammonium chloride, acetic acid and ethanol are added into a reaction kettle and stirred, the temperature of the reaction kettle is increased to 40-60° C., the reaction is kept warm for 2-4 hours, and the modified end-capping agent is obtained by post-processing.

6. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 5, characterized in that: The stirring rate of the reaction kettle is 80-120rpm, the usage ratio of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and 2,3-epoxypropyltrimethylammonium chloride is 1 mol:1 mol, and the usage ratio of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, acetic acid and ethanol is 8-10g:2-3mL:30-40mL.

7. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 3, characterized in that: The preparation method of the modified filler comprises the following steps: C1. Add tetraethoxysilane and anhydrous ethanol into a reaction kettle and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reaction kettle rises to 40-60°C, use 1-1.5 mol / L ammonia solution to adjust the pH of the system to 8-9, and keep warm for 24-36 hours to obtain a silicon-based gel. C2, transferring the silicon-based gel to a tube furnace for calcination to obtain a silicon dioxide polymer, grinding it and passing it through a 400-600 mesh sieve to obtain a modified filler precursor; C3. Add the modified filler precursor, 3-(methacryloyloxy)propyltrimethoxysilane, saturated sodium hydroxide solution and ethanol into the reactor, increase the temperature of the reactor to 30-50° C., keep the temperature for 3-5 hours, and post-treat to obtain the modified filler.

8. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 7, characterized in that: In step C1, the stirring rate of the reactor is 80-120rpm, and the dosage ratio of tetraethoxysilane, anhydrous ethanol and deionized water is 3-6g:30-40mL:10-20mL; in step C2, the calcination operation includes: after nitrogen protection is introduced, the tubular furnace is heated to 450-500°C at a heating rate of 5°C / min, and the silicon dioxide polymer is obtained after calcination for 4-6h; in step C3, the dosage ratio of the modified filler precursor, 3-(methacryloyloxy)propyltrimethoxysilane, saturated sodium hydroxide solution and ethanol is 6-8g:2-3g:0.3-0.5g:30-40mL.

9. The ultra-high hardness antistatic and scratch-resistant polyurethane material according to claim 1, characterized in that: The preparation method of the polyurethane material comprises the following steps: S1, adding composite polyurethane, modified filler, curing agent, antistatic agent, scratch-resistant filler, ultraviolet absorber, dispersant, light stabilizer and rheological agent into a reaction kettle and stirring evenly to obtain a mixture; S2, adding the mixed material into a twin-screw extruder for melt extrusion to obtain a polyurethane material.

Citation Information

Patent Citations

  • Antistatic polyurethane elastomer and its preparation method

    CN108178827B

Cited By

  • Waterborne polyurethane transfer coating for anti-counterfeit label and preparation method of waterborne polyurethane transfer coating

    CN120209662A